2014
DOI: 10.1371/journal.pone.0087984
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Repair and Reduced Mutagenicity of DNA Damage Induced by Cigarette Smoke in Human Bronchial Cells Transfected with E.coli Formamidopyrimidine DNA Glycosylase

Abstract: Cigarette smoke (CS) is associated to a number of pathologies including lung cancer. Its mutagenic and carcinogenic effects are partially linked to the presence of reactive oxygen species and polycyclic aromatic hydrocarbons (PAH) inducing DNA damage. The bacterial DNA repair enzyme formamidopyrimidine DNA glycosylase (FPG) repairs both oxidized bases and different types of bulky DNA adducts. We investigated in vitro whether FPG expression may enhance DNA repair of CS-damaged DNA and counteract the mutagenic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Although U937 and U1 are authentic cell lines for uninfected and HIV-1 infected cell lines, respectively 31 , 48 , we further investigated the effects of CSC/CSC-exosomes on viral replication and cytotoxicity in HIV-1 infected primary human macrophages (PHM) obtained from a healthy donor. Based on the previously described protocol for exosomal entry into macrophages 49 and our uptake study on U937-macrophages (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although U937 and U1 are authentic cell lines for uninfected and HIV-1 infected cell lines, respectively 31 , 48 , we further investigated the effects of CSC/CSC-exosomes on viral replication and cytotoxicity in HIV-1 infected primary human macrophages (PHM) obtained from a healthy donor. Based on the previously described protocol for exosomal entry into macrophages 49 and our uptake study on U937-macrophages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We performed an initial screening of whether U937 monocytic cell-derived exosomes carry CYPs or AOEs (mRNA and/or protein). The role of cellular CYPs and AOEs in tobacco-mediated oxidative stress, cytotoxicity, and carcinogenesis is well-established 48 . Our previous study has also suggested a potential role of CYP and oxidative stress pathways in smoking-mediated HIV-1 replication 24 .…”
Section: Resultsmentioning
confidence: 99%
“…However, in concordance with the results obtained for NPB, NBUDS, APOP, and NECRO, other studies have suggested a protective effect of tobacco exposure via an individual adaptative response in exposed individuals. In vivo evidence has shown that glutathione is elevated in the lung epithelium of mice as a response to inhaled tobacco smoke [ 36 ]. In addition, DNA base excision capacity seems to increase this adaptative response from a mechanical point of view.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of PAH-DNA adducts can be attenuated by detoxification of parent PAHs. PAH-DNA-bound adducts can also be removed by DNA repair processes [ 17 , 18 , 19 , 20 ], and injured cells can be eliminated by cell death including necrosis and apoptosis [ 21 , 22 , 23 ]. During chronic exposures, DNA damage can readily reach steady-state levels in target tissues.…”
Section: Introductionmentioning
confidence: 99%